The Response of Water Dynamics to Long-Term High Vapor Pressure Deficit Is Mediated by Anatomical Adaptations in Plants - Du, Qingjie; Jiao, Xiaocong; Song, Xiaoming; Zhang, Jiayu; Bai, Ping; Ding, Juping; Li, Jianming (Frontiers in Plant Science, 2020)
Vapor pressure deficit (VPD) is the driver of water movement in plants. However, little is known about how anatomical adaptations determine the acclimation of plant water dynamics to elevated VPD, especially at the whole plant level. Here, we examined the responses of transpiration, stomatal conductance (gs), hydraulic partitioning, and anatomical traits in two tomato cultivars (Jinpeng and Zhongza) to long-term high (2.2-2.6 kPa) and low (1.1-1.5 kPa) VPD. Compared to plants growing under low VPD, no variation in gs was found for Jinpeng under high VPD conditions; however, high VPD induced an increase in whole plant hydraulic conductance (Kplant), which was responsible for the maintenance of high transpiration. In contrast, transpiration was not influenced by high VPD in Zhongza, which was primarily attributed to a coordinated decline in gs and Kplant. The changes in gs were closely related to stomatal density and size. Furthermore, high VPD altered hydraulic partitioning among the leaf, stem, and root for both cultivars via adjustments in anatomy. The increase in lumen area of vessels in veins and large roots in Jinpeng under high VPD conditions improved water transport efficiency in the leaf and root, thus resulting in a high Kplant. However, the decreased Kplant for Zhongza under high VPD was the result of a decline of water transport efficiency in the leaf that was caused by a reduction in vein density. Overall, we concluded that the tradeoff in anatomical acclimations among plant tissues results in different water relations in plants under high VPD conditions.